ナンキョクイキ ニ オケル タイキ ジュンカン ト ヒョウショウ ヘノ タイキ ユソウ - 鈴木, 香寿恵; スズキ, カズエ; Suzuki, Kazue (2010)
P(論文) 日本の観測拠点のうち,長期間観測データが蓄積されている沿岸部の昭和基地と,氷床コア掘削地点である内陸部のドームふじ基地を例にとり,それぞれに到達する大気輸送経路の特徴を調べた.大気輸送経路の算出にはNIPR流跡線モデルを用い,ERA-40再解析データを入力データとした.昭和基地については対流圏中層と下層による違いについても調べた. 5日前の空気塊の位置を起源とし,その季節変化を調べた.昭和基地対流圏中層に到達する空気塊は,年間を通じて海起源が約8割を占め,陸起源は2割にとどまっていた.海起源の中では,大西洋起源が約7割となっていた.昭和基地対流圏下層へ到達する空気塊は,海起源と陸起源の比率がほぼ等しく,中層よりもインド洋側・内陸側から西向きの大気輸送が卓越していた.ドームふじ基地へ到達する空気塊の,海・陸起源の比率は昭和基地対流圏下層と同様に半々であるが,一年周期の季節変化がみられた. This study investigate the seasonal variations and features of air transport routes to the Japanese stations, "Syowa Station" and "Dome Fuji Station", which are located on the coastal and in the continental interior, respectively. For backward trajectory calculation, the NIPR trajectory model (NITRAM) and ERA-40 reanalysis were used. At Syowa Station, the difference of air transport between the mid and lower troposphere (500, 850 hPa, respectively) is of interest. We assorted trajectories into four regions by their locations 5-days before, which indicate the origin area of the air parcel. At 500 hPa over Syowa Station, about 80% of air parcels came from the sea, whereas at 850 hPa, half of trajectories came from Antarctica. Generally, air parcels came from west of Syowa Station at 500 hPa (69%). The easterly wind zone covered the station, so air parcels were liable to come from the east and the continental interior at 850 hPa. At 500 hPa over Dome Fuji Station, about 50% of air parcels from the ocean had traveled to the station and there is an annual variation in the origins. departmental bulletin paper